Textual history of the Bible - Feder, Frank,Henze, Matthias,Pajunen, Mika S.,Lange, Armin (Brill, 2020)
The 'Textual History of the Bible' (THB) brings together for the first time all available information regarding the manuscripts, textual history and character of each book of the Hebrew Bible and its translations as well as the deuterocanonical scriptures. In addition, THB covers the history of research, the editorial history of the Hebrew Bible, as well as other aspects of text-critical research and its subsidiary fields, such as papyrology, codicology, and the related discipline of linguistics. 0The 'THB' will consist of 4 volumes. 0Volume 2: Deuterocanonical Scriptures. 0Vol. 2A: overview articles0Vol. 2B: to Ezra0Vol. 2C: Jubilees to 16 Appendix
Literaturverzeichnis: Seite XXV-XXXIX
Keywords: Bibel; Textgeschichte